HILANGNYA BAGIAN TUBUH PASIENYANG MENGAKIBATKAN KECACATAN PERMANEN AKIBAT KELALAIANMEDIS DALAM ASPEK PERTANGGUNGJAWABAN HUKUM - Ni Putu Yuliana Kemalasari; I Putu Harry Suandana Putra (Universitas Mahendradatta, 2023)
The loss of a patient's body part due to the negligence of medical personnel has an impact on intentional disability, thus requiring legal certainty for patients which can be obtained by holding legal responsibility both criminally and civilly to the medical staff due to their negligence. The importance of legal responsibility is to provide legal certainty to patients as victims of negligence by medical personnel resulting in permanent disability. To answer this problem, the legal research method used is normative juridical legal research using a statute approach by examining all laws and regulations related to the legal issues raised. Legal liability due to negligence of medical staff which causes permanent disability in patients can refer to the provisions of Article 1371 paragraph (1) of the Indonesian Civil Code and/or Article 46 of Law no. 44 of 2009 concerning Hospitals in conjunction with Article 190 paragraph (2) of Law no. 36 of 2009 concerning Health. Permanent disability of a patient resulting from the loss of a patient's limbs due to the negligence of public medical personnel is called malpractice. Malpractice is intentional or unintentional error or negligence by medical personnel which causes harm to the health or safety of the patient as a victim. It can be concluded that legal liability which is going to be imposed on medical personnel due to their negligence can be held accountable both criminally and civilly